Modified lignin with high photothermal conversion efficiency and preparation method and application thereof
Through the preparation of modified lignin, the photothermal conversion performance of lignin is improved by inhibiting the accumulation of molecules π-π, and the problem of low photothermal conversion performance of existing lignin is solved, thereby achieving efficient and low-cost photothermal conversion and promotes its application in the fields of seawater evaporators.
Patent Information
- Application Number
- CN202411443932.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-07
AI Technical Summary
The existing lignin has low photothermal conversion performance, resulting in limited application in the field of photothermal conversion materials, and the preparation process and raw materials have not been green, resulting in waste of resources and environmental pollution.
通过将木质素溶解在醇溶剂中萃取,并在碱性溶液中加入甲醛进行反应,制备出高光热转换效率的改性木质素,抑制分子π-π堆积,从而提升其光热转换性能。
It improves the photothermal conversion efficiency of lignin, reaches about 52% temperature heating, is cheap, and realizes the high-value utilization of lignin and environmentally friendly industrial applications. It is suitable for seawater evaporators and other scenarios.
Smart Images

Figure CN119264460A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lignin photothermal conversion, and specifically relates to a modified lignin with high photothermal conversion efficiency and a preparation method and application thereof. Background Art
[0002] Lignin is the second largest biomass resource in the world after cellulose, and is known as one of the most abundant green resources that can be used by humans in the 21st century. However, only a very small amount of industrial lignin has been developed into commercial products, and it is far from being fully utilized. Most of the industrial lignin is piled up or directly incinerated, which not only seriously pollutes the environment, but also causes a large amount of resource waste. Because lignin molecules have a spatial network structure, they play a bonding role in plants and can improve the mechanical strength of the material to a certain extent. In addition, researchers have found that lignin has a high carbon content, has a photothermal effect, and can absorb solar energy in the full spectrum. Therefore, lignin has certain potential in the field of solar-driven photothermal conversion materials. However, to date, there are few studies on the preparation of interfacial evaporation materials using lignin as raw material. Therefore, developing new strategies to solve the low photothermal conversion performance of lignin, realize the low preparation process of photothermal conversion materials and the greening of raw materials, has important social significance and economic value for realizing the high-value utilization of lignin and reducing resource waste and environmental pollution.
[0003] Research shows that when solar energy is captured, it can be converted into various types of energy such as heat, electricity, and chemical energy through photoexcitation. Among them, conversion into heat is a direct conversion process with the highest energy efficiency. Materials absorb electromagnetic radiation and increase their temperature through lattice vibrations or electron oscillations. Based on the electronic structure or band structure of the material, the photothermal conversion mechanism is divided into three categories: plasma resonance heating, non-radiative relaxation of semiconductors, and thermal vibration of molecules.
[0004] Theoretically, the π-π stacking in lignin molecules not only provides power for the self-assembly of molecules, but also promotes non-radiative migration and triggers photothermal conversion. Lignin can perform photothermal conversion, which is attributed to the non-radiative migration promoted by π-π stacking in lignin molecules. Inspired by the interaction of conjugated structures in melanin that contributes to photothermal conversion, the researchers first proved that lignin nanoparticles (L-NPs) can perform photothermal conversion. The authors believe that this is caused by the π-π stacking of lignin molecules. To verify this result, they modified lignin with long alkyl chains to inhibit molecular π-π stacking. The results showed that the photothermal conversion of nanoparticles prepared by modified lignin was reduced. Other researchers compared the photothermal conversion efficiency of alkali lignin (AL), low molecular weight alkali lignin (AOH) and enzymatic lignin (EL). The UV-visible-near infrared spectra of AL, EL and AOH showed that all lignins exhibited single-band absorption characteristics with a maximum absorption peak around 356nm. As the wavelength increases, the light absorption gradually weakens, but it still shows high absorption at 808nm (AL~0.18, EL~0.16, AOH~0.11), indicating that both visible light and near-infrared light can be used as illumination sources for lignin photothermal conversion. Although the order of light absorption of lignin at 808nm is AL>EL>AOH, the photothermal conversion efficiency of AOH is the highest (53.7%), which is higher than most conjugated organic photothermal materials.
[0005] In summary, current scientific and technological workers have revealed that the photothermal effect of lignin mainly comes from the non-radiative migration caused by the π-π stacking between lignin molecules, but its photothermal conversion efficiency is low. In order to improve the light absorption rate of lignin and promote its photothermal conversion, it is necessary to further comprehensively study the main control factors of its photothermal conversion efficiency and realize active regulation. In addition, although the literature has proved the photothermal mechanism of lignin and the factors that may affect the photothermal conversion performance of lignin, there is no literature report on how to develop strategies to improve the photothermal performance of lignin. Therefore, in-depth exploration of the mechanism of enhancing the photothermal performance of lignin has an important impact on broadening the high-value utilization of lignin. Summary of the invention
[0006] In order to solve the low photothermal conversion performance of existing lignin, fill the gap in how to improve the photothermal conversion capacity of lignin, and expand the application of lignin in the field of photothermal conversion materials, the primary purpose of the present invention is to provide a method for preparing modified lignin with high photothermal conversion efficiency.
[0007] Another object of the present invention is to provide a modified lignin with high light-to-heat conversion efficiency obtained by the above preparation method.
[0008] Another object of the present invention is to provide the use of the above-mentioned modified lignin with high light-to-heat conversion efficiency in a seawater evaporator.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing modified lignin with high light-to-heat conversion efficiency comprises the following steps:
[0011] (1) fully dissolving lignin in an alcohol solvent, and then filtering and washing to obtain extracted lignin;
[0012] (2) dissolving the extracted lignin in an alkaline solution to obtain a lignin solution; adding formaldehyde under heating conditions, reacting, filtering and washing, and obtaining modified lignin with high photothermal conversion efficiency.
[0013] Preferably, the lignin in step (1) is at least one of alkali lignin, enzymatically hydrolyzed lignin and lignin sulfonate; more preferably, it is at least one of alkali lignin, enzymatically hydrolyzed lignin and sodium lignin sulfonate.
[0014] Preferably, the alcohol solvent in step (1) is anhydrous ethanol.
[0015] Preferably, the ratio of the lignin to the alcohol solvent in step (1) is 1 g: 40-60 mL; more preferably 1 g: 50 mL.
[0016] Preferably, the purpose of the suction filtration and washing in step (1) is to remove the components of lignin that are insoluble in the alcohol solvent.
[0017] Preferably, the alkaline solution in step (2) is at least one of a sodium hydroxide solution and a potassium hydroxide solution; the concentration of the alkaline solution is 0.01 to 0.05 mol / L; more preferably 0.05 mol / L.
[0018] Preferably, the ratio of the extracted lignin to the alkaline solution in step (2) is 1 g: 5-15 mL; more preferably 1 g: 10 mL.
[0019] Preferably, the heating and reaction temperatures in step (2) are both between 70 and 90°C; more preferably 80°C.
[0020] Preferably, the reaction time of step (2) is 2 to 6 hours; more preferably 4 hours.
[0021] Preferably, the formaldehyde in step (2) is added in two times, and the time interval between the two additions is 1 to 3 hours; more preferably 2 hours.
[0022] Preferably, the formaldehyde in step (2) is added in the form of a formaldehyde solution with a mass concentration of 30-40%, and the ratio of the extracted lignin to the formaldehyde solution is 1 g: 10-30 mL; more preferably 1 g: 20 mL.
[0023] The preparation method mentioned above produces a modified lignin with high light-to-heat conversion efficiency.
[0024] The above-mentioned application of modified lignin with high light-to-heat conversion efficiency.
[0025] Preferably, the modified lignin with high light-to-heat conversion efficiency is used in seawater evaporation.
[0026] More preferably, the modified lignin with high light-to-heat conversion efficiency can be directly used as a seawater evaporator, or can be used as one of the raw materials for preparing a seawater evaporator.
[0027] The present invention utilizes the characteristics of lignin's own photothermal effect to develop a new strategy to improve the photothermal conversion performance of lignin. First, the lignin is fully dissolved in anhydrous ethanol to extract low molecular weight lignin, then the low molecular weight lignin is fully dissolved and a certain amount of formaldehyde solution is added at a certain temperature and fully reacted, and then washed and dried to obtain a modified lignin material with enhanced photothermal effect of lignin.
[0028] Due to the non-radiative migration promoted by π-π stacking in lignin molecules, lignin has a stronger photothermal effect after modification, and the photothermal conversion efficiency of the modified lignin is high, with a higher temperature value under the same lighting conditions, a photothermal conversion efficiency of about 52%, a maximum heating temperature of 112°C and low cost. The prepared modified lignin has a simple production process, a wide source of raw materials, and a low price, which solves the problem that the preparation cost and photothermal performance of existing photothermal materials cannot be achieved at the same time. The modified lignin constructed by the present invention will provide valuable data and reference for subsequent research on the improvement of the photothermal conversion performance of lignin.
[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0030] (1) The present invention uses industrial lignin as raw material, which has a wide source, low price, environmental friendliness, good biocompatibility and degradability, helps to achieve high-value utilization of lignin, and expands the application scope of industrial lignin;
[0031] (2) The reaction conditions of the present invention are simple and mild, and large-scale reactions can be carried out. The raw materials are biomass resources with low toxicity and are environmentally friendly materials. In addition, the photothermal conversion efficiency of the modified lignin obtained is greatly improved, which can reach about 52%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the photothermal heating and cooling curve of Example 6 under one sun intensity.
[0033] Figure 2 This is the photothermal heating and cooling curve of Example 10 under one sun intensity.
[0034] Figure 3 This is the photothermal heating and cooling curve of Example 11 under one sun intensity.
[0035] Figure 4 This is the photothermal heating and cooling curve of comparative example 1 under one sun intensity.
[0036] Figure 5 This is the photothermal heating and cooling curve of comparative example 2 under one sun intensity.
[0037] Figure 6 This is the photothermal heating and cooling curve of comparative example 3 under one sun intensity.
[0038] Figure 7 This is the specific heat capacity test curve of Example 6 in the range of 25°C-120°C.
[0039] Figure 8 This is the specific heat capacity test curve of Example 10 in the range of 25°C-120°C.
[0040] Fig. 9 This is the specific heat capacity test curve of Example 11 in the range of 25°C-120°C.
[0041] Fig.10 This is the specific heat capacity test curve of Comparative Example 1 in the range of 25°C-120°C.
[0042] Fig.11 This is the specific heat capacity test curve of Comparative Example 2 in the range of 25°C-120°C.
[0043] Fig.12 This is the specific heat capacity test curve of Comparative Example 3 in the range of 25°C-120°C. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0045] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0046] Example 1
[0047] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the resulting solution was fully filtered and washed, and the filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 70°C, 5mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and after continuing to stir for 1h, 5mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 1h. The resulting solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-70-10-2, 70 represents the reaction temperature, 10 represents the amount of formaldehyde, and 2 represents the reaction time.
[0048] Example 2
[0049] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the resulting solution was fully filtered and washed, and the filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 70°C, 10mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and after stirring for 1h, 10mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 1h. The resulting solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-70-20-2, 70 represents the reaction temperature, 20 represents the amount of formaldehyde, and 2 represents the reaction time.
[0050] Example 3
[0051] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the resulting solution was fully filtered and washed, and the filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 70°C, 10mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and then stirred for 2h, and then 10mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 2h. The resulting solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-70-20-4, 70 represents the reaction temperature, 20 represents the amount of formaldehyde, and 4 represents the reaction time.
[0052] Example 4
[0053] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the resulting solution was fully filtered and washed, and the filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 80°C, 5mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and after stirring for 1h, 5mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 1h. The resulting solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-80-10-2, 80 represents the reaction temperature, 10 represents the amount of formaldehyde, and 2 represents the reaction time.
[0054] Example 5
[0055] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the resulting solution was fully filtered and washed, and the filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 80°C, 10mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and after continuing to stir for 1h, 10mL of formaldehyde solution (mass concentration of 37%) was continued to be added with a dropper, and then reacted for 1h. The resulting solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-80-20-2, 80 represents the reaction temperature, 20 represents the amount of formaldehyde, and 4 represents the reaction time.
[0056] Example 6
[0057] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the obtained solution was fully filtered and washed, and the obtained filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 80°C, 10mL of formaldehyde solution (mass concentration of 37%) was added to the lignin solution with a dropper, and after stirring for 2h, 10mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 2h. The obtained solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal performance. The photothermal conversion efficiency of the obtained lignin under one sun illumination intensity is about 52%. The lignin is named Lg1-OH-80-20-4, 80 represents the reaction temperature, 20 represents the amount of formaldehyde, and 4 represents the reaction time.
[0058] Example 7
[0059] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the resulting solution was fully filtered and washed, and the filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 90°C, 5mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and after stirring for 1h, 5mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 1h. The resulting solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-90-10-2, 90 represents the reaction temperature, 20 represents the amount of formaldehyde, and 2 represents the reaction time.
[0060] Example 8
[0061] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the obtained solution was fully filtered and washed, and the obtained filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 90°C, 10mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and after stirring for 1h, 10mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 1h. The obtained solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-90-20-2, 90 represents the reaction temperature, 20 represents the amount of formaldehyde, and 2 represents the reaction time.
[0062] Example 9
[0063] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the resulting solution was fully filtered and washed, and the filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 90°C, 10mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and after stirring for 2h, 10mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 2h. The resulting solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal properties. The lignin was named Lg1-OH-90-20-4, 90 represents the reaction temperature, 20 represents the amount of formaldehyde, and 2 represents the reaction time.
[0064] Example 10
[0065] Under magnetic stirring at room temperature, 10g of enzymatic lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the obtained solution was fully filtered and washed, and the obtained filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 80°C, 10mL of formaldehyde solution (mass concentration of 37%) was added to the lignin solution with a dropper, and after stirring for 2h, 10mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 2h. The obtained solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal performance. The photothermal conversion efficiency of the obtained lignin under one sun illumination intensity is about 50%. The lignin is named Lg2-OH-80-20-4, 80 represents the reaction temperature, 20 represents the amount of formaldehyde, and 4 represents the reaction time.
[0066] Embodiment 11
[0067] Under magnetic stirring at room temperature, 10g of sodium lignin sulfonate was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the obtained solution was fully filtered and washed, and the obtained filtrate was fully vacuum dried to obtain the extracted lignin raw material. Weigh 1g of extracted lignin and dissolve it in 10mL of 0.05mol / L NaOH solution, which was completely dissolved. At 80°C, 10mL of formaldehyde solution (mass concentration of 37%) was added dropwise to the lignin solution with a dropper, and then stirred for 2h, and then 10mL of formaldehyde solution (mass concentration of 37%) was added with a dropper, and then reacted for 2h. The obtained solution after the reaction was fully filtered and washed with water to obtain lignin with enhanced photothermal performance. The photothermal conversion efficiency of the obtained lignin under one sun illumination intensity is about 47%. The lignin is named Lg3-OH-80-20-4, 80 represents the reaction temperature, 20 represents the amount of formaldehyde, and 4 represents the reaction time.
[0068] Comparative Example 1
[0069] Under magnetic stirring at room temperature, 10g of alkali lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the obtained solution was fully filtered and washed, and the obtained filtrate was fully vacuum dried to obtain the extracted lignin raw material. The photothermal conversion efficiency of the obtained lignin under the intensity of one sun was about 32%. The lignin was named Lg1, and 1 represented alkali lignin.
[0070] Comparative Example 2
[0071] Under magnetic stirring at room temperature, 10g of enzymatic lignin was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the obtained solution was fully filtered and washed, and the obtained filtrate was fully vacuum dried to obtain the extracted lignin raw material. The photothermal conversion efficiency of the obtained lignin under the intensity of one sun was about 41.84%. The lignin was named Lg2, and 2 represented enzymatic lignin.
[0072] Comparative Example 3
[0073] Under magnetic stirring at room temperature, 10g of sodium lignin sulfonate was weighed and added to 500mL of anhydrous ethanol. After stirring and dissolving, the obtained solution was fully filtered and washed, and the obtained filtrate was fully vacuum dried to obtain the extracted lignin raw material. The photothermal conversion efficiency of the obtained lignin under the intensity of one sun was about 27%. The lignin was named Lg3, and 3 represented sodium lignin sulfonate.
[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing modified lignin with high light-to-heat conversion efficiency, characterized in that: The following steps are involved: (1) fully dissolving lignin in an alcohol solvent, and then filtering and washing to obtain extracted lignin; (2) dissolving the extracted lignin in an alkaline solution to obtain a lignin solution; Formaldehyde is added under heating conditions, reacted, filtered and washed to obtain modified lignin with high light-to-heat conversion efficiency.
2. The method for preparing a modified lignin with high light-to-heat conversion efficiency according to claim 1, characterized in that: Step (2) the formaldehyde is added in the form of a formaldehyde solution with a mass concentration of 30-40%; the ratio of the extracted lignin to the formaldehyde solution is 1 g: 10-30 mL; The lignin in step (1) is at least one of alkali lignin, enzymatic lignin and lignin sulfonate.
3. The method for preparing a modified lignin with high light-to-heat conversion efficiency according to claim 1, characterized in that: The heating and reaction temperatures in step (2) are both 70 to 90° C. and the reaction time is 2 to 6 hours; The formaldehyde in step (2) is added twice, and the time interval between the two additions is 1 to 3 hours.
4. The method for preparing a modified lignin with high light-to-heat conversion efficiency according to claim 1, characterized in that: In step (2), the ratio of the extracted lignin to the alkaline solution is 1 g: 5-15 mL; The alkaline solution in step (2) is at least one of a sodium hydroxide solution and a potassium hydroxide solution; the concentration of the alkaline solution is 0.01 to 0.05 mol / L.
5. The method for preparing a modified lignin with high light-to-heat conversion efficiency according to claim 1, characterized in that: The ratio of the lignin to the alcohol solvent in step (1) is 1 g: 40-60 mL; The alcohol solvent in step (1) is anhydrous ethanol.
6. The method for preparing a modified lignin with high light-to-heat conversion efficiency according to claim 2, characterized in that: Step (2) the formaldehyde is added in the form of a formaldehyde solution with a mass concentration of 37%; the ratio of the extracted lignin to the formaldehyde solution is 1 g: 20 mL; The lignin in step (1) is at least one of alkali lignin, enzymatic lignin and sodium lignin sulfonate.
7. The method for preparing a modified lignin with high light-to-heat conversion efficiency according to claim 1, characterized in that: The heating and reaction temperature in step (2) is 80° C. and the reaction time is 4 h. The formaldehyde in step (2) is added twice, and the time interval between the two additions is 2 hours.
8. A modified lignin with high light-to-heat conversion efficiency obtained by the preparation method according to any one of claims 1 to 7.
9. Application of the modified lignin with high light-to-heat conversion efficiency as claimed in claim 8.
10. The use according to claim 9, characterized in that: The modified lignin with high light-to-heat conversion efficiency is used in seawater evaporation.
Citation Information
Patent Citations
Preparation method of hydroxymethylated lignin
CN106554502A
Preparation method of hydroxymethylated lignin
CN109535441A
Photo-thermal lignin nanoparticle, lignin-based near-infrared light response shape memory polyurethane, and preparation method and application of lignin-based near-infrared light response shape memory polyurethane
CN116535673A
Conjugated reinforced lignin colloidal sphere as well as preparation method and application thereof
CN118063795A